Take a journey to Saga Country, Reykjavik, Iceland - Gislason, Kari (News Limited, 2014)
A travel article about a journey to Reykholt in Western Iceland, once the farm of saga author Snorri Sturluson. A TRIP back into snowbound Iceland's past in search of a famed warrior-poet throws up some old memories and fresh revelations for Kari Gislason "The fish must sing." An odd idea, I know - one uttered by a merchant in a novel by Halldor Laxness. But it said no more than what every Icelander since the settlement had known. If you were going to live on the edge of the world, it paid to do something to remind the rest of the world you were still here.